2016
DOI: 10.3389/fphys.2016.00119
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Is a Key Modulator of Fetoplacental Endothelium Metabolic Disturbances in Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) is a disease of the mother that associates with altered fetoplacental vascular function. GDM-associated maternal hyperglycaemia result in fetal hyperglycaemia, a condition that leads to fetal hyperinsulinemia and altered L-arginine transport and synthesis of nitric oxide, i.e., endothelial dysfunction. These alterations in the fetoplacental endothelial function are present in women with GDM that were under diet or insulin therapy. Since these women and their newborn show nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 124 publications
0
34
0
3
Order By: Relevance
“…TJs have been reported to be present in both trophoblast cells and in fetal vessel epithelium (5). Previous studies have suggested that placental dysfunction in patients with GdM is caused by hyperglycemia (6,7). in addition, other studies have identified that insulin therapy does not improve fetal or newborn metabolic outcomes (8), and that it can cause alterations in the placenta (9), indicating factors other than glucose may be involved in the pathophysiology of GdM.…”
Section: Low Molecular Weight Heparin (Nadroparin) Improves Placentalmentioning
confidence: 99%
“…TJs have been reported to be present in both trophoblast cells and in fetal vessel epithelium (5). Previous studies have suggested that placental dysfunction in patients with GdM is caused by hyperglycemia (6,7). in addition, other studies have identified that insulin therapy does not improve fetal or newborn metabolic outcomes (8), and that it can cause alterations in the placenta (9), indicating factors other than glucose may be involved in the pathophysiology of GdM.…”
Section: Low Molecular Weight Heparin (Nadroparin) Improves Placentalmentioning
confidence: 99%
“…For instance, insulin induces vasorelaxation, enhances endothelial uptake of amino acids (such as L-arginine) and increases survival and migration of endothelial cells (Dubó et al, 2016; Sobrevia et al, 2016). These actions, combined with the capacity of insulin to enhance expression of pro-angiogenic factors such as vascular endothelial growth factor (VEGF), as well as increase pericytes survival and reduce anti-angiogenic protein expression, have established the role of insulin in physiological and pathological angiogenesis (He et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, as nicely reviewed by Eisenstein et al (Eisenstein et al, 2015) there are many opposing findings regarding the role of A 2B AR in metabolic pathologies since this receptor simultaneously and differently affects acute and chronic inflammation (macrophages), adipogenesis (adipose tissue), insulin release (pancreas) and gluconeogenesis as well as glycogenolysis (liver). Additionally, A 2A AR receptors seem essential in developing or maintaining endothelial dysfunction in the fetoplacental vasculature in diseases of pregnancy such as gestational diabetes mellitus or preeclampsia Sobrevia et al, 2016). However, the A 1 AR is required for the effect of insulin correcting the gestational diabetes mellitus-enhanced L-arginine transport in this vascular bed (Guzman-Gutierrez et al, 2016).…”
Section: Distinct Effects On Different Cell Typesmentioning
confidence: 99%